Analytical Steady-State Model for the Free Radical Solution Copolymerization of Acrylonitrile and Vinyl Acetate and Their Charge-Transfer Complex in a Continuous Stirred Tank Reactor - Oscar Meza-Díaz; Juan-Carlos Tapia-Picazo; Adrian Bonilla-Petriciolet; Gabriel Luna-Bárcenas; Daniel Alcalá-Sánchez; José-Enrique Jaime-Leal; Pedro-Jesús Herrera-Franco (International Journal of Chemical Engineering)
In this study, a mathematical model of the copolymerization of AN-VA in a continuous stirred tank reactor (CSTR) was developed considering charge-transfer complexes (CTCs). CTC formation between acrylonitrile (AN) and vinyl acetate (VA) was demonstrated using UV-VIS spectrophotometry and molecular orbital theory. The rate constants and equilibrium constants of the complexes were calculated from a model of the simultaneous participation of complexes and free monomers and the molar ratio method. Furthermore, the participation of CTCs in propagation was included because of their high reactivity. All the simultaneous equations defined to analyze the reactor parameters were analytically solved, and the results of the model were in terms of operative variables such as monomer conversion, average molecular weight, and the mole fraction of monomer 2 (i.e., VA) in the polymer formed. The results of the predictions of the developed model were compared with the experimental data for validation. This prediction was also compared with the reactor model solution without considering the CTC, which showed deviations that were more significant than those of the CTC model. These results represent a quantitative way to analyze the order of magnitude of the impact of the formation of the complexes in the analyzed polymerization system.